Accelerated Skin Wound Healing by Electrical Stimulation. Issue 16 (4th May 2021) - Luo, Ruizeng; Dai, Jieyu; Zhang, Jiaping; Li, Zhou
Abstract: When the integrity of the skin got damaged, an endogenous electric field will be generated in the wound and a series of physiological reactions will be initiated to close the wound. The existence of the endogenous electric field of the wound has a promoting effect on all stages of wound healing. For wounds that cannot heal on their own, the exogenous electric field can assist the treatment. In this review, the effects of exogenous electrical stimulation on wound healing, such as the inflammation phase, blood flow, cell proliferation and migration, and the wound scarring is overviewed. This article also reviews the new electrical stimulation methods that have emerged in recent years, such as small power supplies, nanogenerators (NGs), and other physical, chemical or biological strategies. These new electrical stimulation methods and devices are safe, low‐cost, stable, and small in size. The challenge and perspective are discussed for the future trends of the electrical stimulation treatment in accelerating skin wound healing. Abstract : Electrical stimulation is often used for treatment of skin wounds. The devices used for electrical stimulation is divided into two types‐traditional electrical stimulation devices and new electrical stimulation devices. Electrical stimulation may accelerate the wound healing by shortening the inflammation phase, reducing oedema, increasing blood flow, promoting cells migration, and proliferation and improving the scars.